Euclidean Alignment for Transfer Learning in Multi-band Common Spatial Pattern - Amorim, Marcelo M.; Prata, Leonardo; Maurício, João Stephan; Borges, Alex; Bernardino, Heder; Souza, Gabriel de (Anais da Brazilian Conference on Intelligent Systems (BRACIS); 2024: Anais da XXXIV Brazilian Conference on Intelligent Systems, 2024)
Stroke is a major cause of death and disability worldwide. Motor-Imagery based Brain-Computer Interface (MI-BCI) models offer a post-stroke rehabilitation option. Existing studies for MI-BCI use Transfer Learning techniques like Euclidean Alignment (EA) but lose important brain information due to bandpass filtering. This study introduces new BCI architecture with multi-band temporal filters and EA. The methods considered here are Filter Bank (FB), Empirical Mode Decomposition (EMD), and Continuous Wavelet Transform (CWT). Results show performance improvements, especially with EA being applied before Filter Bank. These models offer promise for post-stroke rehabilitation, particularly when using EA before the multi-band filter.